THE ROLE OF TOURISM COMMUNICATION AND DIGITAL NARRATIVES IN THE AGE OF GLOBAL TRAVEL: The Role of Tourism Communication and Digital Narratives in Shaping Travel Experiences along India's Konkan Sea Coast - Wabale, Vyankatesh; Longani, Kirti; Bacchav, Priyanka (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study explores the role of tourism communication and digital narratives in shaping travel experiences along India's Konkan Sea Coast. Method: Utilizing a qualitative secondary data analysis approach, the research draws on a diverse range of reputable sources including government tourism reports, academic journals, social media content, travel blogs, and digital marketing campaigns. Results: The findings reveal that digital narratives—such as storytelling, visual imagery, and user-generated content—significantly influence tourists’ perceptions, decision-making, and experiential engagement with the Konkan region. These narratives not only emphasize the natural and cultural richness of the coast but also promote emotional connections and community-based tourism. Moreover, the study highlights the growing role of digital communication in encouraging sustainable travel behaviors, including environmental awareness and cultural preservation. Novelty: This research contributes novel insights into how secondary digital content shapes tourism dynamics, offering a nuanced understanding of digital storytelling’s impact on destination branding and responsible tourism along a relatively underexplored coastal corridor in India.